Keylogger Threats in Computer Security Aspects - Samsoni; Ditonius Zebua; Basir; Bayu Aji Pamungkas; Hafidsyah Eka Prayogi; Rifaldie Muhammad; Supri Wahyudi; Wira Samudra (International Journal of Integrative Sciences, 2023)
Along with the development of increasingly advanced technology, the level of need for information security is very important. With the development of information, new problems arise regarding computer security, an example of computer security that often occurs is data theft. Data security in accessing a computer is a form that must be considered both physically and non-physically. One form of data theft crime is recording traces of a computer keyboard with the help of hardware or software. Keylogger is a data theft technique by recording typing on a computer keyboard, by recording when the computer is entered, intruders can enter and steal it. The purpose of this paper is to understand how keyloggers work so that prevention can be carried out by carrying out various kinds of solutions and also to maintain data security systems and know supporting and anti-keylogger software